Rural place branding through social media: a stakeholder strategy perspective - Stylianou, Christiana; Pipyros, Kosmas; Aslanides, Anastasia (My University, 2025)
Purpose: This study explores the strategies employed and challenges faced by various stakeholder groups in Cyprus as they engage in rural place branding through social media. Design/methodology/approach: Qualitative research is used through 14 semi-structured interviews to understand the perspectives of local community representatives, government entities and small business owners and entrepreneurs in rural areas. Findings: The research underscores the crucial importance of social media in strengthening rural place branding. Using strategies such as storytelling, visual content creation and short-form videos, create the identity and visibility of rural areas. Moreover, rural place branding by various stakeholder groups necessitates digital skills upskilling and reskilling and precise online content dissemination and segmentation to address the varied needs of potential visitors. Research limitations/implications: The relative homogeneity of professionals in the sample as well as their background and education, could generate agreement in some areas among respondents, leading to possible limitations in generalisations from the findings of this study. Originality/value: The study was conducted in an island state where social media usage for rural place branding is at a relatively early stage.
Keywords: Qualitative research; Cyprus; Rural place branding; Social media; Stakeholder engagement